2020
DOI: 10.1093/eurheartj/ehaa651
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracoronary infusion of bone marrow-derived mononuclear cells on all-cause mortality in acute myocardial infarction: the BAMI trial

Abstract: Aims  Bone marrow-derived mononuclear cell (BM-MNC) therapy may improve myocardial recovery in patients following acute myocardial infarction (AMI), though existing trial results are inconsistent. Methods and results  Originally an open-label, multicentre Phase III trial, BAMI was designed to demonstrate the safety and efficacy of intracoronary infusion of BM-MNCs in reducing the time to all-cause mortality in patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…So far, cell therapy has been shown to have little effect in patients with acute myocardial infarction (AMI), despite a body of preclinical evidence showing the opposite [ 23 , 24 ]. This has most recently been shown in the Phase III autologous bone marrow cell therapy in acute myocardial infarction trial (BAMI) [ 25 ]. The investigators concluded that the improvement in the standard of care for AMI patients is simply so good that it requires too many patients, close to 10,000, to demonstrate a potential effect of cell therapy on hard end-points such as death.…”
Section: Hydrogel Properties and Delivery Depends On Clinical Indimentioning
confidence: 99%
See 1 more Smart Citation
“…So far, cell therapy has been shown to have little effect in patients with acute myocardial infarction (AMI), despite a body of preclinical evidence showing the opposite [ 23 , 24 ]. This has most recently been shown in the Phase III autologous bone marrow cell therapy in acute myocardial infarction trial (BAMI) [ 25 ]. The investigators concluded that the improvement in the standard of care for AMI patients is simply so good that it requires too many patients, close to 10,000, to demonstrate a potential effect of cell therapy on hard end-points such as death.…”
Section: Hydrogel Properties and Delivery Depends On Clinical Indimentioning
confidence: 99%
“…The investigators concluded that the improvement in the standard of care for AMI patients is simply so good that it requires too many patients, close to 10,000, to demonstrate a potential effect of cell therapy on hard end-points such as death. As an important note, this trial did not meet the number of recruited patients and ended up including 375 out of the planned 3000 [ 25 ]. Since this is caused by the control group, the results will most likely be the same across all cell therapies for AMI.…”
Section: Hydrogel Properties and Delivery Depends On Clinical Indimentioning
confidence: 99%
“…Large-scale, randomized, placebo-controlled trials show only minor benefits, as confirmed by a meta-analysis published in 2015 [ 61 , 62 ]. In addition, the phase III BAMI trial announced in 2020, suffered slow enrollment and failed to demonstrate mortality benefit with BMMNCs [ 63 ].…”
Section: Msc Therapy In Clinical Trialsmentioning
confidence: 99%
“…BAMI trial compared intracoronary infusion of bone marrow-derived mononuclear cells with standard therapy in patients with acute ST elevation myocardial infarction (STEMI) who underwent successful reperfusion therapy [ 11 ]. This randomized, open-label trial enrolled 375 eligible patients and did not show any statistically significant difference in all-cause mortality at 2 years (primary outcomes) and cardiovascular death or hospitalization due to heart failure (secondary endpoint) between the study groups [ 12 ].…”
Section: Other Conference Highlightsmentioning
confidence: 99%